Base metal-catalyzed benzylic oxidation of (aryl)(heteroaryl)methanes with molecular oxygen - Sterckx, Hans; De Houwer, Johan; Mensch, Carl; Herrebout, Wouter; Tehrani, Kourosch Abbaspour; Maes, Bert U. W. (Beilstein Journal of Organic Chemistry, 2016)
The methylene group of various substituted 2- and 4-benzylpyridines, benzyldiazines and benzyl(iso)quinolines was successfully oxidized to the corresponding benzylic ketones using a copper or iron catalyst and molecular oxygen as the stoichiometric oxidant. Application of the protocol in API synthesis is exemplified by the alternative synthesis of a precursor to the antimalarial drug Mefloquine. The oxidation method can also be used to prepare metabolites of APIs which is illustrated for the natural product papaverine. ICP–MS analysis of the purified reaction products revealed that the base metal impurity was well below the regulatory limit.
Keywords: base metal; benzylic; catalyzed; molecular oxygen; oxygenation

(untitled) - Shaabani, A.; Mirzaei, P.; Naderi, S.; Lee, D. G. (Tetrahedron, 2004)

(untitled) - Rathore, R.; Saxena, N.; Chandrasekaran, S. (Synth. Commun., 1986)

European chemicals agency (ECHA) website

(untitled) - Sun, C.-L.; Li, B.-J.; Shi, Z.-J. (Chem. Rev., 2011)

(untitled) - Allen, S. E.; Walvoord, R. R.; Padilla-Salinas, R.; Kozlowski, M. C. (Chem. Rev., 2013)

(untitled) - Shi, Z.; Zhang, C.; Tang, C.; Jiao, N. (Chem. Soc. Rev., 2012)

(untitled) - Punniyamurthy, T.; Velusamy, S.; Iqbal, J. (Chem. Rev., 2005)

(untitled) - Campbell, A. N.; Stahl, S. S. (Acc. Chem. Res., 2012)

(untitled) - Caron, S.; Dugger, R. W.; Ruggeri, S. G.; Ragan, J. A.; Ripin, D. H. B. (Chem. Rev., 2006)

(untitled) - Ojha, L. R.; Kudugunti, S.; Maddukuri, P. P.; Kommareddy, A.; Gunna, M. R.; Dokuparthi, P.; Gottam, H. B.; Botha, K. K.; Parapati, D. R.; Vinod, T. K. (Synlett, 2009)

(untitled) - Moriyama, K.; Takemura, M.; Togo, H. (Org. Lett., 2012)

(untitled) - Jin, C.; Zhang, L.; Su, W. K. (Synlett, 2011)

(untitled) - Pan, J.-F.; Chen, K.-M. (J. Mol. Catal. A: Chem., 2001)

(untitled) - Velusamy, S.; Punniyamurthy, T. (Tetrahedron Lett., 2003)

(untitled) - Bonvin, Y.; Callens, E.; Larrosa, I.; Henderson, D. A.; Oldham, J.; Burton, A. J.; Barrett, A. G. M. (Org. Lett., 2005)

(untitled) - Catino, A. J.; Nichols, J. M.; Choi, H.; Gottipamula, S.; Doyle, M. P. (Org. Lett., 2005)

(untitled) - Pavan, C.; Legros, J.; Bolm, C. (Adv. Synth. Catal., 2005)

(untitled) - Nakanishi, M.; Bolm, C. (Adv. Synth. Catal., 2007)

(untitled) - Zhang, J. T.; Wang, Z. T.; Wang, Y.; Wan, C. F.; Zheng, X. Q.; Wang, Z. Y. (Green Chem., 2009)

(untitled) - Ishii, Y.; Nakayama, K.; Takeno, M.; Sakaguchi, S.; Iwahama, T.; Nishiyama, Y. (J. Org. Chem., 1995)

(untitled) - Moghaddam, F. M.; Mirjafary, Z.; Saeidian, H.; Javan, M. J. (Synlett, 2008)

(untitled) - Zhang, C.; Xu, Z.; Zhang, L.; Jiao, N. (Angew. Chem., Int. Ed., 2011)

(untitled) - Ilangovan, A.; Satish, G. (Org. Lett., 2013)

(untitled) - Zhang, L.; Bi, X.; Guan, X.; Li, X.; Liu, Q.; Barry, B.-D.; Liao, P. (Angew. Chem., Int. Ed., 2013)

(untitled) - De Houwer, J.; Abbaspour Tehrani, K.; Maes, B. U. W. (Angew. Chem., Int. Ed., 2012)

Pharmaceutical Substances - Kleemann, A.; Engel, J.; Kutscher, B.; Reichert, D. (Georg Thieme Verlag, 2001)

(untitled) - Kamijo, S.; Tao, K.; Takao, G.; Tonoda, H.; Murafuji, T. (Org. Lett., 2015)

(untitled) - Liu, J.; Zhang, X.; Yi, H.; Liu, C.; Liu, R.; Zhang, H.; Zhuo, K.; Lei, A. (Angew. Chem., Int. Ed., 2015)

(untitled) - Ren, L.; Wang, L.; Lv, Y.; Li, G.; Gao, S. (Org. Lett., 2015)

(untitled) - Itoh, M.; Hirano, K.; Satoh, T.; Miura, M. (Org. Lett., 2014)

(untitled) - Xie, H.; Liao, Y.; Chen, S.; Chen, Y.; Deng, G.-J. (Org. Biomol. Chem., 2015)

(untitled) - Huang, Y.; Chen, T.; Li, Q.; Zhou, Y.; Yin, S.-F. (Org. Biomol. Chem., 2015)

(untitled) - Sterckx, H.; De Houwer, J.; Mensch, C.; Caretti, I.; Tehrani, K. A.; Herrebout, W. A.; Van Doorslaer, S.; Maes, B. U. W. (Chem. Sci., 2016)

(untitled) - Güven, A. (Int. J. Mol. Sci., 2005)

(untitled) - Adam, S. (Tetrahedron, 1989)

World Health Organization (WHO) website

(untitled) - Schlagenhauf, P.; Adamcova, M.; Regep, L.; Schaerer, M. T.; Rhein, H.-G. (Malar. J., 2010)

(untitled) - Lutz, R. E.; Ohnmacht, C. J.; Patel, A. R. (J. Med. Chem., 1971)

(untitled) - Niwa, T.; Yorimitsu, H.; Oshima, K. (Angew. Chem., Int. Ed., 2007)

(untitled) - Hems, W. P.; Jackson, W. P.; Nightingale, P.; Bryant, R. (Org. Process Res. Dev., 2012)

(untitled) - Genovino, J.; Lütz, S.; Sames, D.; Touré, B. B. (J. Am. Chem. Soc., 2013)

(untitled) - Henderson, R. K.; Jiménez-González, C.; Constable, D. J. C.; Alston, S. R.; Inglis, G. G. A.; Fisher, G.; Sherwood, J.; Binks, S. P.; Curzons, A. D. (Green Chem., 2011)

(untitled) - Prat, D.; Wells, A.; Hayler, J.; Sneddon, H.; McElroy, C. R.; Abou-Shehada, S.; Dunn, P. J. (Green Chem., 2016)

(untitled) - Pieber, B.; Kappe, C. O. (Green Chem., 2013)